Antibiotic resistant bacteria prevalent in livestock and wildlife species in South Africa - Van den Honert, Michaela Sannettha (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhDFoodSc)--Stellenbosch University, 2019.